ROLE OF HUMAN RESOURCE PRACTICESAND STAFF SATISFACTION ONORGANIZATIONAL PERFORMANCE - Alwi, Dr. S Khurram Khan; Shaiq, Dr. Muhammad (The journal of contemporary issues in business and government, 2021)
The study aims to identify the extent at which effective management of HR practices can increase productivity and improve poor performance within the organization. Six major human resource management policies and practices were selected from previous research and analysis was run on a sample of educational institutions of Karachi, Pakistan. Questionnaire,comprised of standard items, wasdeveloped, and circulated in various educational institutions to gather responses. The results generated through the application of SPSS concluded that out of six independent variables, only succession planning and employee satisfaction were found to have a significant impact on organizational productivity. Based on the analysis the study found that educational institutions must pay much more attention to the proper management of their human resources and motivate teachers to realize their skills and competencies to create competitive advantage. To conclude, it could be said that effective management of human resources is very vital to any organization ranging from small to large scare enterprise to sustain productivity.